Information systems success model in mandatory system usage - Monem, Hossein (2013)
The importance of Information System (IS) solutions for organizational competitive advantage has long been recognized but many of the IS implementations are unable to meet the acceptable IS success criteria. In addition, there are many models and frameworks that have been developed to measure and evaluate the success of IS, but none of them considers the role of user, specifically the user quality and personal characteristics. In this study, an IS success model for mandatory system usage that includes the role of user was proposed. The research design adopted a two-phase methodology comprising exploratory and confirmatory phases. The first phase consisted of identification and specification parts whereas the second phase or the confirmation part tested the proposed model. The proposed model was tested in the hospital Laboratory Information Management System (LIMS) which is part of the Hospital Information System (HIS). A survey instrument was developed and distributed to 249 respondents who are the hospital laboratory staff and users of LIMS of three hospitals in Iran. The results of the analysis showed that in the mandatory system usage in the laboratories of hospitals, the impact of the usage quality on the IS net benefits had an insignificant effect. However, the user quality significantly influenced usage quality and satisfaction quality, while their relationships were moderated by personal characteristics. The user qualities which can be manipulated were knowledge management and information technology capabilities, perception, motivation, and training. On the contrary, personal characteristics such as gender, age, education and experience cannot be manipulated during the research. Finally, these qualities have theoretical contribution as they have introduced and detailed the role of user in terms of user quality and personal characteristics in the IS success model for mandatory system usage in the healthcare context.